Analytical Hierarchy Process (AHP) sebagai Sistem Penunjang Keputusan Penerimaan Dosen - Hamsiah Hamsiah (Explorer, 2023)
The selection of new lecturers for a tertiary institution is very important, because it forms the basis for the tertiary institution to have the best quality lecturers, so that they are able to transfer knowledge to students properly, so that the quality of the students produced is also better. In selecting lecturers according to the criteria, disagreements often occur between policy makers so that the results obtained are not in accordance with the goals that have been set. To overcome this, one way that can be applied is to apply a method, namely a decision support system using the Analytical Hierarchy Process (AHP). Education, TKDA, Microteaching, and interviews. The output of this study is a system that can provide alternative recommendations for lecturer acceptance with a consistency index, so that the hierarchy formed is acceptable. Implementation and testing of the system using the super decision application version 2.10. From the four alternative data tested, the best recommendation was Iin Syofia Yandra with a score of 0.37704818, followed by Dori H Putra with a score of 0.23819528